SANITASI PENGOLAHAN DAN PEMERIKSAAN LARVA CACING PITA PADA DAGING ANJING DI RUMAH MAKAN PANGGANG B1 SEKITAR PADANG BULAN SIMPANG SELAYANG MEDAN TAHUN 2013 - evi florida; wirsal hasan; irnawati marsaulina (Lingkungan dan Kesehatan Kerja, 2014)
Sanitary processing and examination taperworm larvae in dog meats in restaurants around padang bulan simpang selayang medan 2013. Various microorganisem can cause disease in humans,either directly or through the intermediaries of the animal (zoonoses),from the class cestoda are parasitic zoonoses including the Echinococcus granulosus transmitted by dog meat which can cause hidaditosis in humans. This study aims to determine the condition of the dog meat hygiene sanitary processing and analyzing the content of larval tapeworm ( Echinococus granulosus ) in dog meat served in restaurant around Padang Bulan Simpang Selayang Medan. The examination conducted in the Laboratory Medilab with muscle compression method and digestive muscles. Results of the study showed that the sanitation principles restourant roast B1 Padang Bulan Simpang Selayang Medan not meet health requirements in accordance with Kepmenkes RI No. 942 / Menkes / SK / VII / 2003 on the principle of processing, keeping, transport, and presentation of meat. At six raw meat samples examined there were two positive samples of raw meat containing tapeworm larvae, after being continued to muscle method, known tapeworm larvaes are still infective. While the meat samples were baked half-cooked and baked until cooked perfectly, there are no larval tapeworms. To break the chain of worm infection in dogs, needs to improve the quality of environment sanitation communities around the residence, and provide good feed for dogs cooked. Besides that dog meat to consumers to cook until the meat perfectly cooked to be consumed on order to avoid paraditic infection. Keywords : Sanitation, ham, taperworm larvae